Synthesis and characterization of a La-Ni/α-Al2O3 catalyst and its use in pyrolysis of glycerol to syngas - Nor Shahirah, Mohd Nasir; Jolius, Gimbun; Su, Shiung Lam; Yun Hau, Ng; Chin, Kui Cheng (Elsevier Ltd, 2019)
The current paper reports on the kinetics of syngas production from glycerol catalytic pyrolysis over Ni/α-Al2O3 catalyst promoted by lanthanum. The 3 wt%La-20 wt%Ni/77 wt%α-Al2O3 catalyst was synthesized and its physiochemical properties were characterized. The BET specific surface area was 2.20 m2.g−1, which was 0.11 m2.g−1 larger than the unpromoted Ni/α-Al2O3catalyst. Significantly, the BET results were supported by the FESEM image which showed that the promoted catalyst has smaller particle size compared to the unpromoted catalyst. The NH3 and CO2-TPD analyses indicates that the catalyst has net acidity with acid:base ratio of 1.12. Catalytic pyrolysis was performed in a 10 mm-ID stainless steel fixed bed reactor with reaction temperatures set at 973, 1023 and 1073 K, employing a weight-hourly-space-velocity (WHSV) of 4.5 × 104 ml g−1 h−1. From reaction studies, the highest glycerol conversion (XG) value was 36.96% at 1073 K. The resulting syngas has H2:CO ratios always lower than 2.0. Subsequently, mechanistic studies indicate that the catalytic glycerol pyrolysis occurred on single catalytic site via associative adsorption, with molecular surface reaction as the rate-determining step.